Transformation of phenolic compounds of pyrolysis bio-oil to high-value chemicals by catalytic hydrotreatment / Hoda Shafaghat - Hoda, Shafaghat (2016)

(untitled)
Pyrolysis bio-oil is recognized as a renewable and carbon-neutral fuel which could be potential alternative for depleting fossil fuels. However, bio-oil is highly oxygenated and needs to be upgraded prior to be used as fuel/fuel additive. Catalytic hydrodeoxygenation (HDO) is an efficient technique for bio-oil upgrading. The reaction pathway for HDO of bio-oil is unknown since it is a mixture of hundreds of different compounds. The study on mechanism of transformation of these compounds could be helpful to propose an overall pathway for HDO of bio-oil. Phenols which are derived from pyrolysis of lignin fraction of biomass are considered as attractive model compounds for study of bio-oil HDO since they are highly stable in HDO reaction. Reaction pathway and product selectivity in HDO of phenols are highly affected by catalyst type and process conditions. Bifunctional catalysts consisting of metal and acid sites are usually used for transformation of bio-oil/bio-oil model compounds to valuable hydrocarbons. Metal and acid sites are generally involved in hydrogenation/hydrogenolysis and dehydration/hydrocracking/dealkylation/alkylation/isomerization reaction mechanisms, respectively. In this work, product selectivity of hydrogenation of phenol, o-cresol, m-cresol and guaiacol (the most abundant phenolics of bio-oil) was investigated over combined catalysts of Pd/C with zeolite solid acids of HZSM-5 (Si/Al of 30, 50 and 80) and HY (Si/Al of 30 and 60) in an autoclave batch reactor. Catalytic activity and product distribution were affected by density and strength of zeolite acid sites. Meanwhile, bifunctional metal/acid catalysts of 5 wt% Ni/HBeta, 5 wt% Fe/HBeta, 2.5 wt% Ni-2.5 wt% Fe/HBeta (NiFe-5/HBeta) and 5 wt% Ni-5 wt% Fe/HBeta (NiFe-10/HBeta) were used for HDO of a phenolic bio-oil simulated by mixing phenol, o-cresol and guaiacol. Cycloalkanes and aromatic hydrocarbons were the dominant hydrocarbons obtained over monometallic catalysts of Ni/HBeta and Fe/HBeta, respectively. Bimetallic catalyst of NiFe/HBeta showed enhanced HDO efficiency compared with monometallic catalysts of iv Ni/HBeta and Fe/HBeta due to the synergistic effect between the two metals. The effect of reaction temperature on HDO efficiency of NiFe-10/HBeta catalyst was investigated. Replacement of water with methanol as solvent in HDO of the simulated phenolic bio-oil over NiFe-10/HBeta remarkably reduced the selectivity towards hydrocarbons. High flammability of hydrogen gas in contact with air leads to difficult control of high pressurized hydrogen gas in large-scale systems. Meanwhile, molecular hydrogen production is a costly industrial process. Thus, hydrogenation study using hydrogen donor (H-donor) material as alternative for hydrogen gas could be useful in terms of cost and safety control. In this study, the potential of decalin and tetralin for use as hydrogen source was investigated in transfer hydrogenation of renewable lignin-derived phenolic compounds (phenol, o-cresol and guaiacol) and a simulated phenolic bio-oil over Pd/C and Pt/C catalysts. Reaction mechanisms of H-donor dehydrogenation and phenolics hydrogenation were studied. Furthermore, the influence of water content on transfer hydrogenation activity was studied by employing the water to donor ratios of 0/100, 25/75, 50/50 and 75/25 g/g. The catalysts used in this research were characterized by N2 adsorption, XRF, XRD, NH3-TPD, H2-TPD and TGA, and liquid products were analyzed using GC-MS.